Preferensi Pemilih Milenial Dalam Menentukan Pilihan Pasangan Welly-Parulian Pada Pemungutan Suara Ulang (PSU) Tahun 2025 (Studi Kasus Kecamatan Rao Kabupaten Pasaman) - Riko Riyanda; Angelina Putri Giawa; Tesha Dwi Putri; Lara Indah Yandri; Khairiyah Khairiyah (Asosiasi Ide Bahasa Kepri, 2026)
The victory of the Welly-parulian pair in the PSU ini Rao subdistrict cannot be separated from the support of the millenial vote. with a significant number of elihible voters in this demographic, Millenial behavior Will be an interesting study to determine the basis of millenial voters preferences in selecting candidates, ultimately allowing Welly-parulian to defeat the incumbent candidate in the Pasaman regional election. this paradox is unusual in regional election, as incumbents are typically very difficult to be defeated by new pairs. This study aims to analyze the political preferences of millennial voters in choosing the Welly-Parulian candidate pair during the 2025 Repeat Voting (PSU) in Rao District, Pasaman Regency. Millennial voters as the majority group of voters have different characteristics, namely in terms of access to information, use of technology, and political decision-making. The analysis is based on Afan Gaffar’s theory of voter behavior, which categorizes voting approaches into three types: sociological, psychological, and rational approaches. The results of the study indicate that the political preferences of millennial voters in Rao District are predominantly shaped by the rational approach, in which voters logically and critically assess the vision, mission, work programs, and track record of the Welly-Parulian candidate pair before making their decision. The millennial generation tends to rely on rational considerations in their political choices, reflecting a growing political awareness based on information and practical needs.